Fibrinolytic Protease Activity of Crude Enzyme from Fermented Sunflower (Helianthus annuus) and Common Bean (Phaseolus vulgaris) seeds by Rhizopus microsporus var. oligosporus FNCC 6010 in Solid State Fermentation - Rebhika Lusiana; Achmad Toto Poernomo; Achmad Syahrani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
In the entire world, cardiovascular diseases (CVDs) are the main cause of death. For the treatment of CVDs, microbial fibrinolytic enzymes are highly regarded as novel therapeutic candidates. This study was purposed to determine the fibrinolytic protease activity produced by fungus source, which is Rhizopus microsporus var. oligosporus FNCC 6010 in fermented sunflower (Helianthus annuus) seed and common bean (Phaseolus vulgaris) seed. Fermentation was carried out by solid-state fermentation method at an initial pH of 5, incubation temperature of 33±1°C, and incubation time of 24 hours. The fermented seed was extracted to obtain supernatant as the crude enzyme. The proteolytic activity assay was done by the skimmed milk agar (SMA) plate method to obtain the proteolytic index, and the fibrinolytic activity assay was conducted by the fibrin-agarose plate method to get the fibrinolytic index. The results show that crude enzymes from fermented H. annuus and P. vulgaris seeds by R. microsporus have fibrinolytic protease activity with proteolytic index 2.64 ± 0.01 and 2.23 ± 0.04, respectively. The fibrinolytic index is 2.40 ± 0.06 and 1.64 ± 0.06, respectively. Therefore, the crude enzyme has the potential to be further researched as a candidate for thrombolytic agents. The purification, characterization, and in-depth research are needed to develop enzymes into preparations for preventing and treating CVDs.